Variation of tumoral marker after radiofrequency ablation of pancreatic adenocarcinoma - D’Onofrio, Mirko; Barbi, Emilio; Girelli, Roberto; Tinazzi Martini, Paolo; De Robertis, Riccardo; Ciaravino, Valentina; Salvia, Roberto; Butturini, Giovanni; Frigerio, Isabella; Milazzo, Teresa; Crosara, Stefano; Paiella, Salvatore; et al. (Journal of Gastrointestinal Oncology; Vol 7, No 2 (April 01, 2016): Journal of Gastrointestinal Oncology, 2015)
Background: To evaluate the correlation between variations of CA 19.9 blood levels and the entity of necrosis at CT after radiofrequency ablation (RFA) of unresectable pancreatic adenocarcinoma. Methods: In this study, from June 2010 to February 2014, patients with diagnosis of unresectable and not metastatic pancreatic ductal adenocarcinoma, expressing tumor marker CA 19.9, treated with RFA procedure were included. All these patients underwent RFA. CT study was performed 1 week after RFA. The dosage of CA 19.9 levels was performed 1 month after RFA. Features of necrosis at CT, as mean entity, density and necrosis percentages compared to the original lesion, were evaluated and compared by using t-test with CA 19.9 blood levels variations after RFA procedure. Results: In this study were included 51 patients with diagnosis of unresectable and not metastatic pancreatic ductal adenocarcinoma, expressing tumor marker CA 19.9, treated with RFA procedure and with CT study and CA 19.9 available for analysis. After the procedure, CA 19.9 blood levels reduced in 24/51 (47%), remained stable in 10/51 (20%) and increased in 17/51 (33%). In patients with CA 19.9 levels reduced, the tumor marker were reduced less than 20% in 4/24 (17%) and more than 20% in 20/24 (83%); instead the tumor marker were reduced less than 30% in 8/24 (33%) and more than 30% in 16/24 (67%). At CT scan necrotic area density difference was not statistically significant. Also there was no statistically significant difference among the mean area, the mean volume and the mean ablation volume in percentage related to the treated tumor among the three different groups of patients divided depending on the CA 19.9 blood levels. But a tendency to a statistically significant difference was found in comparing the mean percentage of ablation volume between two subgroups of patients with a decrease of CA 19.9 levels with less or more than 20% reduction of tumor markers and between two subgroups with less or more than 30% reduction of CA 19.9 levels. Conclusions: RFA of unresectable pancreatic adenocarcinoma induces reduction of CA 19.9 blood levels in about half of the cases.